2010
DOI: 10.1063/1.3328885
|View full text |Cite
|
Sign up to set email alerts
|

State-resolved reactivity of CH4 on Pt(110)-(1×2): The role of surface orientation and impact site

Abstract: The reactivity of methane (CH(4)) on Pt(110)-(1 x 2) has been studied by quantum state-resolved surface reactivity measurements. Ground state reaction probabilities, S(0)(v=0) congruent with S(0)(laser-off), as well as state-resolved reaction probabilities S(0)(2nu(3)), for CH(4) excited to the first overtone of the antisymmetric C-H stretch (2nu(3)) have been measured at incident translational energies in the range of 4-64 kJ/mol. We observe S(0)(2nu(3)) to be up to three orders of magnitude higher than S(0)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
64
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 35 publications
17
64
1
Order By: Relevance
“…They noted that their data did not rule out the possibility of a precursor-mediated reaction channel involving vibrationally hot methane molecules, but suggested that at low E trans , CH 4 molecules might be steered into a particularly low-barrier or barrier-less reaction path that could dramatically enhance reactivity. More recent state-resolved experiments of CH 4 dissociation on Pt(1 1 0)-(1 × 2) confirm the low-E trans reactivity reported by Walker and co-workers for molecules without laser excitation, but S 0 for molecules in the 2 3 vibrational state (2 quanta of C-H stretch) appear to react via a direct reaction mechanism at all E trans between 4 and 62 kJ/mol [21].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…They noted that their data did not rule out the possibility of a precursor-mediated reaction channel involving vibrationally hot methane molecules, but suggested that at low E trans , CH 4 molecules might be steered into a particularly low-barrier or barrier-less reaction path that could dramatically enhance reactivity. More recent state-resolved experiments of CH 4 dissociation on Pt(1 1 0)-(1 × 2) confirm the low-E trans reactivity reported by Walker and co-workers for molecules without laser excitation, but S 0 for molecules in the 2 3 vibrational state (2 quanta of C-H stretch) appear to react via a direct reaction mechanism at all E trans between 4 and 62 kJ/mol [21].…”
Section: Introductionsupporting
confidence: 56%
“…Observation of a collision-induced reaction pathway implicated methane's bending vibrations in promoting reaction [15]. Since that time, the range of surfaces explored with conventional beam-surface scattering techniques has expanded to include Pt(1 1 1) [16][17][18], Pt(1 1 0)-(1 × 2) [19][20][21], Pt(5 3 3) [22], Ni(1 0 0) [23], Ru(0 0 0 1) [24,25], Ir(1 1 1) [26,27], Ir(1 1 0) [28,29] Pd(1 1 0) [30] and mixed metal systems such as Cs/Pt(1 1 1) [31], Co/Cu(1 1 1) [32] and Au/Ni(1 1 1) [33]. The majority of these studies reveal that S 0 increases monotonically and nearly exponentially with increasing E trans over the range of E trans explored.…”
Section: Introductionmentioning
confidence: 99%
“…To determine absolute reaction probabilities for CH 4 , we perform a timed exposure of the clean crystal surface to the molecular beam, measuring both the incident dose of CH 4 molecules per unit area with the calibrated QMS as well as the resulting coverage of carbon reaction products on the surface by performing calibrated AES measurements across the surface in a computer-controlled scan. 16 We measured the state-resolved reactivity of CH 4 , prepared in the four different vibrational states shown in Table I; each containing different amounts of C-H stretch and bend excitation given approximately by their zero-order normalmode labels ͑ 1 and 3 are the symmetric and antisymmetric stretch modes and 2 and 4 are IR-inactive and IR-active bend vibrations, respectively͒. Because of the near degeneracy of the stretch fundamentals and bend overtones, the vibrational states of CH 4 can be grouped into polyads of nearly isoenergetic vibrational states 17 ͑Fig.…”
mentioning
confidence: 99%
“…The state-resolved reactivity for E t Ͻ 10 kJ/ mol has been discussed elsewhere. 16 While the 2 2 + 4 , 1 + 4 , and 3 + 4 states have similar vibrational energy ͑Table I͒, they result in different reactivities. Furthermore, the 1 + 4 and 2 3 states have similar reactivities even though their vibrational energy is different.…”
mentioning
confidence: 99%
“…For example, on Ni(111) and Pt(111), the minimum barrier is calculated for dissociation over the top site (90). Bisson et al (91) exploited shadowing effects on a corrugated Pt(110)-(1×2) surface to control the impact site of incident methane in order to measure the relative reactivity of ridge and trough sites. To do this, they determined the polar-angle dependence of the CH 4 (ν 3 ) reactivity for incidence parallel and perpendicular to the close-packed rows of Pt atoms.…”
Section: Role Of Incidence Angle and Impact Sitementioning
confidence: 99%